HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN GUGUS 4 KECAMATAN LIMAPULUH KOTA PEKANBARU - Apri Alwina; Syahrilfuddin '; Muhammad Fendrik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: One of several factor which influenced learning achievement is interest. This study aims to determine the relationship between student interest in student learning outcomes in mathematics fifth grade students of SDN Cluster 4 Districts Limapuluhkota Pekanbaru. Pebelitian methods are correlational. Mechanical sampling using cluster. Methods of data collection using a scale and technical documentation of the value of MID second semester. The analysis technique used is the technique of analysis Product Moment. Test requirements analysis in the form of normality and linearity test. Engineering analysis and test requirements analysis using SPSS 20. Results of research is conducted indicates that there is a relationship between interest in learning the mathematics learning outcomes fifth grade students of SDN group 4 Districts Limapuluhkota Pekanbaru obtained rxy of 0.374 with a low correlation level and also interest in learning to give effect to the results studied at 14%. Dioeroleh t test results obtained thitung 3.722 and 1.663 ttabel this case shows that there is a significant relationship between interest in learning the mathematics learning outcomes fifth grade students of SDN Cluster 4 Districts Limapuluhkota Pekanbaru.Keywords: Interest In Learning, Mathematic Achievement